Influence of spirituality on renal function of kidney transplant patients - Bravin, Ariane Moyses [UNESP]; Trettene, Armando dos Santos [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; Banin, Vanessa Burgugi [UNESP]; Moura Ribeiro Paula, Niura Aparecida de [UNESP]; Saranholi, Tais Lopes [UNESP]; Popim, Regina Celia [UNESP]; Modelli de Andrade, Luis Gustavo [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2017)
Objective: To evaluate influence of spirituality on renal function of kidney transplant patients. Methods: This cross-sectional study included 81 kidney transplant patients who had undergone transplantation between 30 and 60 months previously. Patients were followed up for 12 months. The analysis was carried out in a large public hospital in the countryside of Sao Paulo, Brazil. Based on the Duke University Religion Index-religiosity and spirituality scale, we divided patients into two groups (spiritualized [n=52] and less spiritualized [n=29]), considering the median spirituality. For statistical analysis, we used inductive tests and analysis with linear mixed models, with a level of significance of 5% (p<0.05). Results: Clinical characteristics, immunosuppression, social support, adherence to drug therapy, quality of life, and depression did not differ between groups. Renal function after 12 months was significantly higher in the spiritualized group from 9 months on. After 12 months, the percentage of patients with creatinine clearance higher than 60 ml/min was 61.5% in the spiritualized group and 34.5% in the less spiritualized group (p=0.02). Multivariate analysis showed that the less spiritualized group had a 4.7 times greater risk [1.4 - 16.8] for worsening in renal function (p=0.01). Conclusion: More spiritualized patients had better renal function after 1 year of transplantation. This result was independent of clinical features, social support, and adherence to immunosuppressive therapy. A holistic approach in health with emphasis on spirituality is encouraged.
Keywords: Spirituality; Kidney transplantation; Chronic disease; Religion; Religion and medicine